PENGARUH BAHAN BAKAR PERTALITE MURNI DENGAN CAMPURAN BAHAN BAKAR PREMIUM DAN PERTAMAX TERHADAP PERFORMANCE EMISI GAS BUANG PADA MOTOR HONDA BEAT 2017 - Setiawan, Joni; Ghofur, Abdul (JTAM ROTARY, 2022)
Performance and exhaust emissions in 2017 Honda Beat vehicles, namely: 1. The best exhaust emissions are produced in a mixture of 50% premium fuel and 50% first with HC value of 23 ppm, CO 0.31%, CO2 5.88% and O2 11.30%. So the more mixture of pertamax at the premium, the better the exhaust emissions produced. 2. The best performance is produced in a mixture of 50% premium fuel and pertamax 50% with a torque value of 11.01 in Rp. 3655 and a power of 7,537 HP at Rp. 6994. So the more mixture of pertamax at the premium, the better exhaust emissions produced. 3. Performance and exhaust emissions, pure pertalite produces the best performance and exhaust emissions compared to the mixture of premium and pertamax fuel with a torque value of 11.57 Nm at rpm 3680, power 7,555 HP at rpm 7136, HC 11 ppm, CO 0.27%, CO2 is 5.36% and O2 is 11.48%.